2021
DOI: 10.1111/dmcn.14830
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of physical activity participation for young people and adults with childhood‐onset physical disability: a mixed methods systematic review

Abstract: To understand the attitudes, barriers, and facilitators to physical activity participation for young people and adults with childhood-onset physical disability.METHOD Seven electronic databases (Embase, MEDLINE, PsychINFO, AMED, CINAHL, SPORTDiscus, and ERIC) were searched to November 2019. English language studies were included if they investigated attitudes, barriers, or facilitators to physical activity for young people (≥15y) or adults with childhood-onset physical disabilities. Two reviewers applied eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 81 publications
(484 reference statements)
1
32
0
1
Order By: Relevance
“…Reasons for this inactivity could be due to different factors like physical impairments, but probably the lack of knowledge and life skills, limited availability of transport and professional guidance as well as social support plays a role (11). McKenzie et al (12) concluded in a systematic review that (young) adults struggle to find the right balance to be physically active because of their social and physical environment. However, since these studies are mainly focused on HIC, little is known about the influence of cultural and socio-economic factors on the level of an individual's PA in resource-limited settings such as South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for this inactivity could be due to different factors like physical impairments, but probably the lack of knowledge and life skills, limited availability of transport and professional guidance as well as social support plays a role (11). McKenzie et al (12) concluded in a systematic review that (young) adults struggle to find the right balance to be physically active because of their social and physical environment. However, since these studies are mainly focused on HIC, little is known about the influence of cultural and socio-economic factors on the level of an individual's PA in resource-limited settings such as South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…integração e a socialização pelas trocas de ideias e experiências vividas, e esse convívio fortalece as relações pessoais no dia a dia (AMARAL FILHO et al, 2013). A boa intervenção por parte do profissional de saúde ( VAN der PLOEG et al, 2004), aliada à positiva influência social, opinião e comportamento da sociedade, são fatores determinantes para o envolvimento das pessoas com deficiência nos programas de exercícios ou esportivos (MACKENZI et al, 2021). Facilitadores como, gostar das atividades realizadas, sentir prazer na prática, não apresentar timidez ou preguiça, dispor de tempo e não vivenciar experiências negativas foram elencados por 1191 pessoas com deficiência intelectual que frequentavam as Associação de Pais e Amigos dos Excepcionais (APAES) do Rio Grande do Sul (JUNG et al, 2017).…”
Section: Resultsunclassified
“…Social construction theory was applied to the construct of disability to suggest the meaning ascribed by society to physical, cognitive, mental, and emotional impairments [28]. According to this theory, disability cannot exist independently of the context within From these three accessible belief systems, behavioural intention is the immediate antecedent of a particular behaviour.…”
Section: Social Construction Of Disability and Barriers To Sport And Pa Engagementmentioning
confidence: 99%